Generation of a human induced pluripotent stem cell line harboring the infant leukemia-associated fusion gene, KMT2A-AFF1 (IMSUTi002-A-2) - Masayuki Takahashi (Stem Cell Research, 2023)
KMT2A-AFF1 (MLL-AF4), formed by chromosomal translocation t(4;11), is observed specifically in infant pro-B acute lymphoblastic leukemia, and the main driver of leukemogenesis. In this study, a human induced pluripotent stem cell (hiPSC) line harboring KMT2A-AFF1 (IMSUTi002-A-2), which has the ability to simultaneously induce the doxycycline-inducible expression of KMT2A-AFF1 and EGFP, was established. This hiPSC can be a powerful model for understanding infant leukemia and risk assessment of leukemogenesis.